Kelopak Jaya Enterprise: a case study on problems during ladders making / Mohd Alif Ezani ... [et al.] - Ezani, Mohd Alif; Nik Abdul Halim, Nik Muhd Hanif; Mohamed Sari, Muhammad Azlan (2017)
The aim to conducting this case study at the KJ Enterprise is to identified the potential problem of the company based of the SWOT analysis and Consumer Trend Canvas. In this study, we chose the company because it is still new and need more changes to develop to become bigger. This company has potential to place their product in a better market such as the overseas market. To ensure this „ company is able to maintain and fulfill the demand in the future, a few technological solutions is needed to be implemented so that the current problem able to be solved without disturbing the company's production and costing. The data that are collected in this study is only based on observation, interview and preview of the document and previous record that been provided from the company. All of the data collected will be analyzed and the solution will be given in order to overcome the problems of the company. The interview has been carried out to understand the real situation that happens in the company.